2017
DOI: 10.33588/rn.6405.2016395
|View full text |Cite
|
Sign up to set email alerts
|

Traducción y validación de la escala Individualized Neuromuscular Quality of Life para la población española: evaluación de la calidad de vida para personas afectas de enfermedades neuromusculares

Abstract: con la salud en individuos con enfermedades neuromusculares. Pacientes y métodos. Se realiza una traducción-retrotraducción de la INQoL en la población española y, posteriormente, para el análisis de fiabilidad se llevan a cabo dos mediciones, test-retest, a 50 pacientes de 19 a 67 años. De este modo se evalúa la concordancia intraobservador y se evalúa la consistencia interna de la escala. Resultados. El estudio de la fiabilidad del índice de concordancia intraobservador tiene un valor de excelente en siete d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…When comparing these results with those of one study that was conducted with NMD and assessed with INQoL, the patients with LGMD-D2 are found to have higher scores on the impact of muscle pain and fatigue [33]. In another study in which patients with NMD were assessed using INQoL, it was observed that in the present sample, they had higher fatigue impact scores [34].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…When comparing these results with those of one study that was conducted with NMD and assessed with INQoL, the patients with LGMD-D2 are found to have higher scores on the impact of muscle pain and fatigue [33]. In another study in which patients with NMD were assessed using INQoL, it was observed that in the present sample, they had higher fatigue impact scores [34].…”
Section: Discussionsupporting
confidence: 54%
“…Another important aspect recognized in the present study is that age seems to correlate with a greater involvement of the disease in activities of daily living and emotional management. Age as an influential variable in the worsening of disease symptoms is seen in other chronic pathologies [33]. The underlying explanation for this relationship seems to be that the specific pathophysiological mechanisms that cause clinical disorders are modified by an aging process [34].…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in 17 generic and 14 diseasespecific PROMs out of 190, which we have further described in Table 2. Only ten PROMs, the Activity Limitations Measure (ACTIVLIM) (in different types of NMD) [21][22][23][24][25], Amyotrophic Lateral Sclerosis Assessment Questionnaire (ALSAQ-40) (in ALS) [26][27][28][29][30][31][32][33][34][35], ALSAQ-5 (in ALS) [28,29,33,36], Childhood Health Assessment Questionnaire (CHAQ) (in jDM and jIIM) [37][38][39][40][41], Child Health Questionnaire psychosocial summary score (CHQ-ps) (in juvenile dermatomyositis) [38], Dyspnea-ALS-Scale (DALS-15) (in ALS) [42,43], Health Assessment Questionnaire-Disability Index (HAQ-DI) (in myositis) [44], Individualized Neuromuscular Quality of Life Questionnaire (INQoL) (in different types of NMD) [45][46][47][48][49], Inflammatory Rasch-built Overall Disability Scale ((I-RODS) (in Chronic Inflammatory Demyelinating Polyneuropathy, Guillain Barre Syndrome, Monoclonal gammopathy of undetermined significance) [50][51][52][53], and Patient-Reported Outcomes Measurement Information System Physical Function (PROMIS PF20) (in myositis) [44], were sufficiently evaluated for all psychometric characteristics (when statistical psychometric indexes met COSMIN's quality criteria). Table…”
Section: Resultsmentioning
confidence: 99%